2015
DOI: 10.1080/10790268.2015.1117193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differences in age and body height on normal values of central motor conduction time determined by F-waves

Abstract: Objectives: To investigate the effect on central motor conduction time (CMCT) based on the relationship between age and height in normal subjects. Design: Retrospective study. Methods: One hundred and ninety nine normal subjects (107 men and 92 women; mean age 39.0 ± 16.4 years; mean height 164.5 ± 8.8 cm) participated in the study. The approximate ages of subjects were as follows: 82 (20-29 years old), 32 (30-39 years old), 32 (40-49 years old), 28 (50-59 years old), and 25 (≧60 years old). The heights of 9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…The ADM control data came from a previously published study. 1 No significant correlations were found between the CMCT-APB and the CMCT-ADM (CMCT-APB -CMCT-ADM) = 0.1±1.0 ms (P = 0.44).…”
Section: Deep Tendon Reflex and Hoffmann Signmentioning
confidence: 82%
See 1 more Smart Citation
“…The ADM control data came from a previously published study. 1 No significant correlations were found between the CMCT-APB and the CMCT-ADM (CMCT-APB -CMCT-ADM) = 0.1±1.0 ms (P = 0.44).…”
Section: Deep Tendon Reflex and Hoffmann Signmentioning
confidence: 82%
“…The central motor conduction time (CMCT) has been used to electrophysiologically evaluate corticospinal tract function and is very useful for diagnosing corticospinal tract disorders. [1][2][3][4] Measurement of the CMCT is noninvasive and safe for investigating lateral corticospinal tract function. In our previous study, we found a systematic correlation between the CMCT recorded from the abductor digiti minimi (ADM; CMCT-ADM) and the responsible level of cervical compressive myelopathy (CCM).…”
Section: Introductionmentioning
confidence: 99%
“…the Motor Evoked Potentials (MEPs) to evaluate the corticospinal tract integrity at screening (T(− 1)); MEPs will be recorded from the bilateral Abductor Digiti Minimi (ADM) muscle by following the methodology reported in [29]. In brief, TMS will be delivered in single stimuli at maximum output stimulator (5 stimuli for each side) and electromyographical (EMG) activity will be recorded from ADM muscle bilaterally, if allowed during voluntary contraction.…”
Section: Neurophysiological Assessmentmentioning
confidence: 99%
“…UMN involvement was defined based on the findings of increased/hyperactive deep tendon reflexes (DTR) and/or pathological reflexes (i.e., in the upper extremity: palmomental and Hoffmann signs, and in the lower extremity: Babinski sign), in the neurological examination or abnormal findings in transcranial magnetic stimulation (TMS), i.e., absent or reduced motor evoked potential or prolonged central motor conduction time adjusted to the height of the subject (Groppa et al, 2012;Imajo et al, 2017). DTR was determined according to DTR scale (0: no response, 1+: sluggish, 2+: normal, 3+: slightly hyperactive/brisk, 4+: abnormally hyperactive with intermittent clonus) (Seidel et al, 2011).…”
Section: Participant Selectionmentioning
confidence: 99%